Function spaces in modern analysis : Sixth Conference on Function Spaces, May 18-22, 2010, Southern Illinois University, Edwardsville - Conference on Function Spaces; Jarosz, Krzysztof (Contemporary mathematics, 2011)
This volume contains the proceedings of the Sixth Conference on Function Spaces, which was held from May 18-22, 2010, at Southern Illinois University at Edwardsville. The papers cover a broad range of topics, including spaces and algebras of analytic functions of one and of many variables (and operators on such spaces), spaces of integrable functions, spaces of Banach-valued functions, isometries of function spaces, geometry of Banach spaces, and other related subjects.